2009
DOI: 10.1080/09638280902751972
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a Web-based stroke intervention on carers' well-being and survivors' use of healthcare services

Abstract: This Web-based intervention helped new carers make informed decisions about healthcare needs of stroke survivors, thus reducing service use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
224
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(236 citation statements)
references
References 22 publications
4
224
1
7
Order By: Relevance
“…Future studies should be responsive and tailored to both the needs of the care of the survivor and the unique needs of the family caregiver. 25,27,38,40,41,[44][45][46][47][48][49][50][51][52][53][54][55][56][58][59][60][61] 17 (53.1) 4 (23.5) 16 (94) Stroke survivor-caregiver dyad 26,[28][29][30][31][32][33][35][36][37]39,42,43,57,62,63 15 ( Psycho-educational 26,29,33,37,39,42,58 7 (21.9) 6 (85.7) 6 (85.7)Skill building and psycho-educational 25,27,28...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should be responsive and tailored to both the needs of the care of the survivor and the unique needs of the family caregiver. 25,27,38,40,41,[44][45][46][47][48][49][50][51][52][53][54][55][56][58][59][60][61] 17 (53.1) 4 (23.5) 16 (94) Stroke survivor-caregiver dyad 26,[28][29][30][31][32][33][35][36][37]39,42,43,57,62,63 15 ( Psycho-educational 26,29,33,37,39,42,58 7 (21.9) 6 (85.7) 6 (85.7)Skill building and psycho-educational 25,27,28...…”
mentioning
confidence: 99%
“…Only a few published studies accessed long-term outcomes. 48,57 Access to Experts Access to experts was specifically mentioned relative to several studies 38,59,61 and may have been available but not clearly identified in other interventions. Experts may include such individuals as case managers, nurses, therapists, social workers, psychologists, and in some cases, expert caregivers.…”
mentioning
confidence: 99%
“…In two cases, STAR in the EU and AlzOnline in the US, the outcome improvements were quite weak, concerning only better empathy feeling between caregivers and intervention staff [18] and selfefficacy [19]. One study, focused on the Caring Web program for family caregivers of stroke survivors [23], conducted a RCT involving 103 users but without demonstrating improvements in psychological outcomes, showing instead significant reductions in emergency department visits and hospital readmissions.…”
Section: Evidence Psychoeducational Programsmentioning
confidence: 99%
“…Bakım vericileri geliştirme, güçlendirmeye yönelik bu girişimler maliyet etkili olduğu için uygulanabilir. 22,24,27,28,30,31,36 İnme öz yönetimini artırmak için yapılan bir çalışma, 10 hafta iki saatlik grup eğitimlerinden oluşmaktadır. Uygulanan öz yönetim programının en önemli sonuçlarından biri, bakım verenlerin topluma katılım oranındaki artıştır.…”
unclassified